UJI EFEKTIVITAS DAUN KEMBANG BULAN (Tithonia diversifolia (Hemsl.) A. Gray) TERHADAP PERTUMBUHAN Trichophyton rubrum SECARA IN VITRO - Salsabila Febriani Damli (2023)
A common health problem especially in tropical countries is fungal infections of the skin, hair and nails. The most common fungal skin infection is dermatophytosis. Trichophyton rubrum is the species that most commonly causes dermatophytosis. Tithonia diversifolia (Hemsl.) A. Gray is one of the plants whose health benefits have been clinically shown. Moonflower leaves have several compounds that have potential as antifungal. This study aims to determine the effectiveness of T. diversifolia (Hemsl.) A. Gray leaf extract against the growth of T. rubrum in vitro. The research used was experimental research with Post Test-Only Control Group design. Antifungal test using the well diffusion method with Sabouraud Dextrose Agar media. The results showed that T. diversifolia (Hemsl.) A. Gray leaf extract can inhibit the growth of T. rubrum at concentrations of 6.25%; 12.5%; 25%; and 50% with the highest average value of inhibition zone of 12.57 mm. Kruskal-Wallis test obtained significance 0.00 (p<0.05) and Post Hoc Mann-Whitney test p<0.05 in each concentration comparison. The conclusion of this study is that T. diversifolia (Hemsl.) A. Gray leaf extract contains alkaloid, saponin, flavonoid, tannin and phenol compounds that can damage the fungal cell wall so that it has effectiveness against the growth of T. rubrum in vitro. The most effective concentration of extract in inhibiting the growth of T. rubrum is 50% concentration and can be classified as a strong antifungal. Keywords: Antifungal, Tithonia diversifolia (Hemsl.) A. Gray, Trichophyton rubrum, Zone of inhibition.